Handbook of Immunosenescence 2019
DOI: 10.1007/978-3-319-99375-1_66
|View full text |Cite
|
Sign up to set email alerts
|

Role of Zinc and Selenium in Oxidative Stress and Immunosenescence: Implications for Healthy Aging and Longevity

Abstract: Aging is a complex process that includes gradual and spontaneous biochemical and physiological changes which contributes to a decline in performance and increased susceptibility to diseases. Zn and Se are essential trace elements that play a pivotal role in immune functions and antioxidant defense and, consequently, are claimed to play also a role in successful aging trajectories. Eugenio Mocchegiani has retired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 231 publications
(249 reference statements)
0
6
0
Order By: Relevance
“…Apart from being a cofactor for numerous enzymes, they play the key role in the development and functioning of the central nervous system [ 24 , 25 , 26 ]. Disturbed homeostasis and distribution of TEs related to anti-oxidant, anti-inflammatory, and apoptotic effects seem to be connected with neurodegenerative diseases and aging [ 27 ]. Disturbances in Cu homeostasis lead to impaired neuronal function and neurological diseases, including Alzheimer’s disease and Wilson’s disease [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from being a cofactor for numerous enzymes, they play the key role in the development and functioning of the central nervous system [ 24 , 25 , 26 ]. Disturbed homeostasis and distribution of TEs related to anti-oxidant, anti-inflammatory, and apoptotic effects seem to be connected with neurodegenerative diseases and aging [ 27 ]. Disturbances in Cu homeostasis lead to impaired neuronal function and neurological diseases, including Alzheimer’s disease and Wilson’s disease [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…An investigation carried out by Zhang et al [8] showed that the levels of environmental Se were very low, and Kaschin-Beck disease in the Tibetan Plateau was much severe with decreasing environmental Se under the Se-deficient condition, suggesting the relationship between Kaschin-Beck disease and Se deficiency in the Tibetan Plateau. In addition, Se is related to other human diseases and health, such as cancer [10][11][12][13], muscle disease [14], and healthy aging and longevity [15][16][17]. Therefore, it is essential to maintain Se homeostasis in human body [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to SCFA, selenium protects DNA, and it has been suggested that Se slows the aging process by protecting DNA against reactive oxygen species [ 91 ]. Both postbiotics and minerals such as selenium and zinc exhibited antioxidant activities [ 92 ].…”
Section: Mineral-enriched Postbiotics and Their Applications In Micro...mentioning
confidence: 99%